Adenocarcinoma in females detected in serous effusions: Cytomorphologic aspects and immunocytochemical reactivity to cytokeratins 7 and 20 - Longatto Filho, Adhemar; Bisi, Hélio [UNESP]; Alves, Venâncio Avancini Ferreira [UNESP]; Kanamura, Cristina Takami; Oyafuso, Marina Suheko; Bortolan, Jeni; Lombardo, Valéria (Karger Publishers, 1997)
OBJECTIVE: To investigate the usefulness of assessing the immunoreactivity of cytokeratins 7 (CK7) and 20 (CK20) as well as several cytomorphologic parameters in effusions with metastatic adenocarcinomas in the search for the primary site of the tumor. STUDY DESIGN: From the files of the Pathology Department, A. C. Camargo Hospital, we studied cytologic smears from 73 metastatic adenocarcinomas originally from the breast, 63 from the ovary, 40 from the lung and 32 from the stomach, looking for morphologic parameters that could have discriminant potential in suggesting the primary site in a routine situation, including intranuclear inclusions, prominent nucleoli, mitosis, signet-ring cells, psammoma bodies, nuclear crease, binucleation and multinucleation, papillary features, acinar profile (including ball cells) and single cells. Immunoreactions were performed with monoclonal antibodies to CK7 (OV-TL 12/30 and CK20 (Ks 20.8) and included morphologic analysis. Both analyses were studied in a blind fashion regarding the primary site of the tumors. RESULTS: Positivity ratios for breast, ovary, stomach and lung cases were 67.6%, 63.5%, 29.7% and 45.5%, respectively, for CK7 and 17.2%, 15.8%, 13.5% and 32.2%, respectively, for CK20. Discriminant analysis of morphologic and immunocytochemical parameters had an error rate of 42.9% in recognizing the primary site and a Wilk's lambda of .7290. CONCLUSION: The more efficient parameter with discriminant function was the papillary appearance showed by CK7, which should be used in further studies with a similar scope. The set of parameters used in this study were insufficient to discriminate the primary site of female adenocarcinomas in effusions with significant accuracy.
Keywords: Adenocarcinoma; Cytokeratin; Immunocytochemistry; cytokeratin; cytokeratin 20; cytokeratin 7; unclassified drug; adenocarcinoma; breast carcinoma; cancer cytodiagnosis; cancer localization; clinical article; effusion; female; human; intermediate filament; lung carcinoma; metastasis; ovary carcinoma; priority journal; stomach carcinoma; Breast Neoplasms; Female; Humans; Immunohistochemistry; Intermediate Filament Proteins; Keratin-20; Keratins; Lung Neoplasms; Neoplasms, Unknown Primary; Ovarian Neoplasms; Serous Membrane; Stomach Neoplasms; Tumor Markers, Biological